Supplementary Material to: Skyrmion Deformation under the Antiferromagnetic System - Xiuzhu Wang (11843588) (2025)
This is the Supplementary Material for Skyrmion Deformation under the Antiferromagnetic System, which includes additional information on the derivations and supplementary simulations mentioned in the main text.